Non-genetic impact factors on chronological lifespan and stress resistance of baker’s yeast - Michael Sauer; Diethard Mattanovich (Microbial Cell)
Survival under nutrient limitation is an essential feature of microbial cells, and it is defined by the chronological lifespan. We summarize recent findings, illustrating how crucial the choice of the experimental setup is for the interpretation of data in this field. Especially the impact of oxygen supply differs depending on the culture type, highlighting the differences of alternatives like the retentostat to classical batch cultures. Finally the importance of culture conditions on cell aging and survival in biotechnological processes is highlighted.